Impact of nutritional therapy during the first wave of the COVID-19 pandemic in intensive care patients: A retrospective observational study. Issue 12 (December 2022) - de Watteville, Aude; Montalbano, Florencia; Wozniak, Hannah; Collet, Tinh-Hai; Jaksic, Cyril; Le Terrier, Christophe; Pugin, Jérôme; Genton, Laurence; Heidegger, Claudia Paula
Summary: Background & aims: The COVID-19 pandemic has caused major organizational challenges to healthcare systems concerning staff, material and bed availability. Nutrition was not a priority in the intensive care unit (ICU) at the beginning of the pandemic with the need for simplified protocols. We aimed to assess the impact of a simplified nutritional protocol for critically ill COVID-19 patients during the pandemic first wave. Methods: We included all patients with SARS-CoV-2 infections, admitted to the ICU of the Geneva University Hospitals for at least 4 days from March 9 to May 19, 2020. Data on the route and solution of nutritional therapy, prescribed and received volume, calorie and protein intake, amount of insulin, propofol and glucose administered were collected daily during the entire ICU stay. We compared nutritional outcomes between patients admitted to the ICU before and after implementing the simplified nutritional protocol using unpaired t-test. Results: Out of 119 patients, 48 were hospitalized in the ICU before, 47 across and 24 after the implementation of the nutritional protocol. The mean age was 63.2 (±12.7) years and 76% were men without significant difference between before and after group. The nutritional protocol implementation led to an increase in caloric intake (1070 vs. 1357 kcal/day, p = 0.018) and in the percentage of days within 80–100% of the energy target (11 vs. 20%, p = 0.021). The protein debt decreased significantly from 48 g/day to 37 g/day (p = 0.015). No significant difference in the percentage of days within the protein target (80–100%) was observed. Conclusions: Calorie and protein coverage improved after the implementation of the simplified nutritional protocol in critically ill COVID-19 patients. Further studies are needed to assess the impact of such an approach on patients' clinical outcomes.